Penanaman Nilai-nilai Pendidikan Karakter dalam Pembelajaran Sejarah Kelas X SMA - Firhan Miftahul Aziz; Ba’in; Fendi Aditiya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study was to analyze the implementation of character education values ​​in history lessons in grade 10 students at SMA Negeri 1 Parakan, identify the applied character values, and analyze the supporting and inhibiting factors. This study used a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusion drawing. The results indicate that the implementation of character education has been carried out in an integrated manner through the planning, implementation, and evaluation stages of learning. The character values ​​developed include religiousness, nationalism, discipline, responsibility, honesty, mutual cooperation, communication, independence, social awareness, and environmental awareness. Successful implementation was supported by teacher commitment, school culture, and facilities and infrastructure. Challenges encountered included differences in student character and motivation, limited learning time, use of gadgets, and family background. The study indicates that history lessons are an effective medium for internalizing character education values ​​through an integrated and sustainable learning process. Keywords: Character Education, Character Values, High School, History Learning, Implementation.